Problematika Keterbacaan Kitab Turats Fiqh Fathu al-Qarib Di Kelas Program Kitab Turats Plus (KTP) Pondok Pesantren Salaf Modern Thohir Yasin - Iwan Hadi Saputra; Mustafa Bin Che Omar; Suparmanto Suparmanto (The Center for Language Development, Mataram State Islamic University., 2023)
Kitab Turats Fiqh Fathu al-Qarib is a book in the Syafi'iyyah school of thought which is always studied and taught in the world of Islamic boarding schools. Along with the development of time, this book has always been a reference standard in measuring the fluency and understanding of students in reading kitab turats. So the level of readability of this book is closely related to the level of difficulty encountered when reading the book. Therefore, this study aims to analyze the readability problems contained in this book, especially among students of the class of the Kitab Turats Plus (KTP) program at Thohir Yasin Salaf Modern Islamic Boarding School. This study uses a qualitative method with a case study research design. The research data collection instruments were interviews and documentation with fifteen informants. Meanwhile, in analyzing the data, this study used the Atlas.ti 9.0 application using the thematic analysis method. The results of this study found that students still experienced difficulties in analyzing and applying nahwu and sharf knowledge in the kitab Fathu al-Qarib. In addition, the cause of student's difficulties in reading and understanding the kitab Fathu al-Qarib is that there is still a lack of mastery and memorization of vocabulary and there are still difficulties with fiqh terms, especially those found in the chapter on zakat and the latter is due to the lack of parental support, the difference in cognitive level between one student and another and due to the activities of the Islamic boarding school too dense. Therefore, recording and evaluating any difficulties faced by students in reading kitab turats is highly recommended for teachers so that the goals to be achieved can be efficient and on target.